Hemodynamic and thrombogenic analysis of a trileaflet polymeric valve using a fluid–structure interaction approach. Issue 13 (15th October 2015) - Piatti, Filippo; Sturla, Francesco; Marom, Gil; Sheriff, Jawaad; Claiborne, Thomas E.; Slepian, Marvin J.; Redaelli, Alberto; Bluestein, Danny
Abstract Surgical valve replacement in patients with severe calcific aortic valve disease using either bioprosthetic or mechanical heart valves is still limited by structural valve deterioration for the former and thrombosis risk mandating anticoagulant therapy for the latter. Prosthetic polymeric heart valves have the potential to overcome the inherent material and design limitations of these valves, but their development is still ongoing. The aim of this study was to characterize the hemodynamics and thrombogenic potential of the Polynova polymeric trileaflet valve prototype using a fluid–structure interaction (FSI) approach. The FSI model replicated experimental conditions of the valve as tested in a left heart simulator. Hemodynamic parameters (transvalvular pressure gradient, flow rate, maximum velocity, and effective orifice area) were compared to assess the validity of the FSI model. The thrombogenic footprint of the polymeric valve was evaluated using a Lagrangian approach to calculate the stress accumulation (SA) values along multiple platelet trajectories and their statistical distribution. In the commissural regions, platelets were exposed to the highest SA values because of highest stress levels combined with local reverse flow patterns and vortices. Stress-loading waveforms from representative trajectories in regions of interest were emulated in our hemodynamic shearing device (HSD). Platelet activity was measured using our platelet activation state (PAS) assay and the results confirmed the higher thrombogenic potential of the commissural hotspots. In conclusion, the proposed method provides an in depth analysis of the hemodynamic and thrombogenic performance of the polymer valve prototype and identifies locations for further design optimization.